HETEROSIS IN CGMS AND GMS BASED CHILLI (CAPSICUM ANNUUM L.) HYBRIDS FOR GREEN FRUIT YIELD, ITS COMPONENTS AND QUALITY TRAITS - BHAUMIK R. PATEL; B. R. PATEL; A. PARIHAR; RAMESH; DIXITA PATEL (The Bioscan, 2015)
Chilli (Capsicum annuumL.) is an important commercial spice cum vegetable crop of Solanaceae family. Due to wide variability, it holds potential for further improvement. The present investigation on chilli comprised of 5 females (2 CGMS and 3 GMS), 8 males, 40 F1 hybrids and two standard check hybrids GAVCH 1 and ARCH-228. The experiment was laid out in randomized block design with 3 replications at Main Vegetable Research Station, Anand Agricultural University, Anand Campus, Anand, during kharif-rabi 2011-2012. This results suggested that differences in performance of parents and hybrids for majority of the traits leading to evidence for manifestation of heterosis for green fruit yield and majority of its components. On the bases on estimates of heterosis, the hybrids ACMS 4 X 9955-15R, CCA-4759 X LCA 206 and CCA-4759 X RHRC PENDT were found to be most promising for green fruit yield and other desirable traits, hence could be further evaluated to exploit the heterosis for commercial cultivation or utilize in future breeding programme to obtain desirable segregants for the development of superior genotypes